The effect of bond market transparency on bank loan contracting - Chy, Mahfuz; Kyung, Hoyoun (Journal of Accounting and Economics, 2023)
We find that bond issuers receive bank loans with 12% fewer covenants when the secondary corporate bond market becomes more transparent. The treatment effect is more pronounced when bond trades are more informative, when stock prices are less informative, and when the likelihood of future debt-equity agency conflicts is higher. The evidence suggests that bond prices reflect forward-looking information that mitigates banks’ information risk in debt contracting. As such, banks impose fewer contractual restrictions on bond issuers when bond transactions become publicly observable. We find consistent results using a hand-collected dataset of negative covenants. Treatment firms are also less likely to subsequently renegotiate borrowing terms. Finally, we find corroborating evidence from new primary bond issues. Taken together, our findings suggest that public bond market frictions affect private debt contract design.